Performance Analysis on a Solar Thermoelectric Refrigerator - 罗斌; 代彦军 (Zhileng xuebao)
The basic structure of a thermoelectric refrigerator driven by solar cells was described. A theoretical model of a solar thermoelectric refrigerator was set up and numerical simulation of the system was performed. The effect of different solar insolation rate and velocity of air on solar thermoelectric refrigeration system was analyzed. The results indicate that there is an optimum solar insolation rate,at which the system can achieve maximum cooling production. When the solar insolation rate is about 200-1000 W/m2,COP for the specified system decreases with the decrease of insolation rate. Under given conditions,the system working current increases in the direction of the optimum system working current with the increase of air velocity.